Cover Image, Volume 51, Issue 2 - Miolo, G. (Cell Prolif, 2018)
The cover image, by G. Miolo et al., is based on the Original Article 4,6,4'‐trimethylangelicin shows high anti‐proliferative activity on DU145 cells under both UVA and blue light, DOI 10.1111/cpr.12430. [Image: see text]